2012
DOI: 10.1161/atvbaha.112.252130
|View full text |Cite
|
Sign up to set email alerts
|

Extrahepatic High-Density Lipoprotein Receptor SR-BI and ApoA-I Protect Against Deep Vein Thrombosis in Mice

Abstract: Objective Deep vein thrombosis (DVT) and pulmonary embolism are frequent causes of morbidity and mortality. We wished to determine whether plasma high density lipoprotein (HDL), which inversely correlates with the risk of cardiovascular events, affects DVT. Methods and Results Using a murine DVT model of inferior vena cava stenosis, we demonstrate that deficiency of the HDL receptor, scavenger receptor class B type I (SR-BI), promotes venous thrombosis. As SR-BI−/− mice have increased plasma cholesterol leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 54 publications
6
40
0
Order By: Relevance
“…Recently, it has been shown that, in vivo, apoA‐I deficiency abrogates flow restriction–induced thrombosis in a mouse model of deep vein thrombosis, and intravenous human apoA‐I infusion in wild‐type mice decreases thrombi prevalence from 55% in vehicle‐infused mice to 0% 51. Figure 8A shows representative aggregation curves, obtained with a Chrono‐log Optical aggregometer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been shown that, in vivo, apoA‐I deficiency abrogates flow restriction–induced thrombosis in a mouse model of deep vein thrombosis, and intravenous human apoA‐I infusion in wild‐type mice decreases thrombi prevalence from 55% in vehicle‐infused mice to 0% 51. Figure 8A shows representative aggregation curves, obtained with a Chrono‐log Optical aggregometer.…”
Section: Resultsmentioning
confidence: 99%
“…VWF has been implicated in the pathogenesis of this disorder in epidemiologic studies 42,43 and in animal models. [44][45][46] ApoA-I protects mice from venous thrombosis, partly by suppressing endothelial activation, 47 presumably reducing VWF secretion. 18 In summary, we describe an important anti-adhesive, anti-thrombotic role for HDL/ApoA-I: the ability to interfere with VWF self-association and thereby reduce the length and thickness of VWF fibers, decreasing platelet adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…35 It should be noted, however, that there is significant variability in thrombosis observed in the IVC stenosis model. 35,53,[70][71][72] One study reported increased incidence of thrombosis in this model in C57BL/6J mice bearing subcutaneous PANC02 tumors. 73 In contrast, we did not observe an increase in IVC thrombosis in nude mice bearing TF-positive human HPAF-II pancreatic tumors.…”
Section: Tf-positive Mps In Animal Studiesmentioning
confidence: 93%